Indicadores colaborativos de Educación Ambiental y ecoeficiencia para el campus la Matriz de la Universidad Técnica de Cotopaxi 2023. - Flores Asimbaya, Dierzaa Carolina (2023)
The presence of Environmental Education in curricular training and the development of eco efficient measures that promote care for the environment are scarce at universities. The objective of this research work is to develop collaborative indicators of Environmental Education and Eco-efficiency that strengthen environmental processes on the La Matriz campus of the Cotopaxi Technical University through the execution of a diagnosis, bibliographic review, and the application of the PER model (pressure, status, response). Firstly, we applied 14 interviews on Environmental Education to the campus directors, whichwere coded through the Altas.ti program, in addition, 58 surveys to campus departments questioning the management of office supplies and the consumption of water, electricity, fossil fuels, and connectivity, then with the application of the PER method according to the information collected and the construction of the system of indicators. As a result of the investigation, we evidenced that Environmental Education on the La Matriz campus is limited, at the curricular, budgetary, and investigative levels; in the field of eco-efficiency less than 50% of the offices recycle and reuse, the level of water consumption is acceptable, but there is high consumption of electricity, paper and plastic. Based on the diagnosis and bibliographic compilation, we generated a collaborative system made up of 50 indicators, 22 corresponding to eco-efficiency and 28 to Environmental Education. In conclusion, the use of the system of indicators would encourage institutional sustainable development because the university community at La Matriz does not receive adequate information, awareness, or environmental culture.